THE CAPABILITY OF LOCAL GOVERNMENT IN SAGO DEVELOPMENT: EFFORTS TO SUPPORT FOOD SECURITY IN THE REGENCY OF MERANTI ISLANDS - Rafi, M.; Ardiansyah, Ardiansyah; Purnomo, Eko Priyo; Handoko, Tito; Rahmat, Al Fauzi (Department of Government, FISIP, Universitas Padjadjaran, 2021)
Government efforts to support food security have been made through various potentials in the agricultural sector, such as sago development as a locally-based alternative food source. However, the facts show that sago can only be used as a second staple food and requires adequate local government capacity in its development. This study uses a qualitative method with a literature study approach. Data collection techniques used are documentation techniques in journals, proceedings, books, government websites, and online news related to various government strategies in developing sago. The results showed that the Meranti Islands Government had socialized the